Establishment of a donor pig for xenotransplantation clinical trials based on the principle of Changsha Communiqué - Xiaoqian Ma; Sang Li; Jia Wang; Chang Xu; Wei Wang (Wiley, 2023)
Abstract Background Xenotransplantation is a potential way to reduce the shortage of the needed organ grafts for the end‐stage disease. Immune rejection, physiological incompatibility and bio‐safety are the most critical issues. Methods To ensure the safety and efficacy of gene editing, second‐ and third‐generation sequencing technologies have allowed us to obtain a clearer genetic background of donor pigs for xenotransplantation. Based on the Changsha Communiqué, the local DPF‐ excluded lists and DPF donor facility were established in Changsha, China. A pig‐to‐human islet clinical trial was conducted and overseen by the respective Chinese governmental agency. Results The DPF standards for pig husbandry eliminated specific pathogens in donor pigs. We have established a PERV‐C free, genetic information clean, DPF donor for xenotransplantation. A clinical trial of ten adult patients (9M:1F) with type 1 diabetes who received DPF porcine islet xenotransplantation via the portal vein were performed. Clinical accepted immunosuppressant drugs and autologous Treg were used for controlling immune rejection. No cross‐species infection events occurred in this trial, and importantly, no cross‐species transmission of PERV was found. Conclusions Xenotransplantation is a pioneer study and safety is the most important issue. The fundamental principles for establishing xenotransplantation donor pigs should follow the Changsha Communiqué (2008), the second WHO consultation,and the 2018 Changsha Communiqué which would finally help reducing the risks of xenotransplantation.